Interannual variability of diurnal tide in the tropical mesopause region: A signature of the El Nino-Southern Oscillation (ENSO) - Gurubaran, S.; Rajaram, R.; Nakamura, T.; Tsuda, T. (My University, 2005)
[1] Long-term MLT radar observations of the diurnal tide at 86 km over Jakarta (6.4°S, 106.7°E) and Tirunelveli (8.7°N, 77.8°E) during the years 1993–1999 are examined in this work. Monthly estimates of tidal amplitudes in the meridional direction over these sites reveal a pronounced interannual variability. The satellite derived Outgoing Longwave Radiation (OLR) is used as a proxy for deep tropical convection in this study. Removal of composite seasonal cycle yields ‘anomalies’ in the diurnal tide over Jakarta and Tirunelveli that are correlated with the OLR anomalies over the western Pacific region (∼120°E). It is suggested that the lower atmospheric large-scale convective systems originating over the western Pacific region in response to the El Nino Southern Oscillation (ENSO) facilitate excitation of nonmigrating tides through latent heat release or large-scale redistribution of water vapor that compete with the dominant migrating tide and possibly induce the observed interannual variability in the diurnal tide.
Keywords: Interannual variability; Tropical mesopause region; El Nino-Southern Oscillation (ENSO); MLT radar; Outgoing Longwave Radiation (OLR)